Wolvers - Brown, Taylor, 1982- (St. Martin's Press, 2026)
"From the Southern Book Prize winning author of Rednecks: a thrilling novel of pursuit, survival, and redemption between two species in the American Southwest. Broke, dispossessed, and angry at the government after losing his family's New Mexico ranch, Trace Temple is looking for revenge. He's living out of his truck when a shadowy militia movement hires him to take down the legendary she-wolf of the Dark Canyon pack, One-Eleven. But One-Eleven is no ordinary wolf. Cunning, fiercely protective of her young, and seasoned in the ways of men, she leads her pack deep into the forbidding desert peaks and canyons, always one step ahead of pursuit. After a harrowing brush with death in the backcountry, Trace has a change of heart-only to be replaced by a professional hunter and assassin named Murdoch, who ruthlessly pursues his animal quarry while stalking Trace himself. To survive, Trace must join forces with a pair of unlikely allies: a survivalist animal protector who deploys feral senses and deep wilderness skills to protect the wolves, and Imogen Cruz, a local rancher, childhood friend, and unrequited love of Trace's early years. Together, they must fight to protect not only themselves and the Dark Canyon pack, but ultimately, the Gila Wilderness itself-the world's first designated wilderness area. In Wolvers, award-winning author Taylor Brown presents a suspenseful, thrillingly-written tale set at the burning edge of today's Southwest, where once-extinct wolves have returned, the land is tinder-dry and fragile, and desperate men seek to reclaim what they believe is theirs to rule"-- Provided by publisher.